Influence of Nb Dopant Concentration on the Structural Properties and Photocatalytic Performances of Hydrothermally Synthesized ZnO for Multi-Pollutant Degradation - Quratul Aini; Carenina Isabel Suwono Putri; Rima Nurfitria; Istiara Rizqillah Hanifah (Green and Sustainable Materials Society, 2026)
The development of effective photocatalysts for multi-pollutant wastewater remediation remains a significant environmental concern. In this study, Nb-doped ZnO photocatalysts with different Nb concentrations (0-6%) were synthesized using a hydrothermal process to systematically examine the influence of dopant concentration on materials characteristics and photocatalytic performance. According to X-ray diffraction analysis Nb incorporation preserved the hexagonal wurtzite ZnO structure with only slight lattice parameter changes, suggesting limited substitutional doping. Morphological observations showed that moderate Nb doping slightly enhanced particle structure and reduced agglomeration. The photocatalytic activity was evaluated through the degradation of ciprofloxacin (CIP) and methylene blue (MB) under UV irradiation, both in single and mixed pollutant systems. In single systems, the catalysts achieved high degradation efficiencies of up to 93.09% for CIP and 92.03% for MB after 120 min. In the mixed system, the efficiencies slightly decreased due to competitive interactions, reaching up to 87.57% (CIP) and 84.08% (MB). Kinetic analysis indicates pseudo-first-order behavior, with apparent rate constants (k) of approximately 0.0218 min−1 (CIP) and 0.0199 min−1 (MB) for the optimally doped Nb4-ZnO sample, which are comparable to those of pristine ZnO. The findings highlight the critical role of dopant concentration in tailoring structural and electronic properties, providing valuable insights into Nb-dopant optimization strategies for efficient multi-pollutant photocatalytic wastewater remediation.